Role of commuting characteristics on physical and mental health among members at university institutions (DiNaMo-active): a protocol for an observational study - Uwe Tegtbur; Sven Haufe; Johanna Boyen; Mailin Beyer; Sarah Wussow-Hampel; Lothar Stein; Lea Sophie Schmidt (BMJ Open Sport & Exercise Medicine)
Insufficient physical activity is associated with numerous widespread diseases, productivity loss, and sick leave at the workplace. A physically active way to work is a potential resource for implementing regular physical activity into daily life. However, there is a lack of data on the duration and physical exertion involved and the potential health benefits of physically active commuting compared with passive commuting.Digitalisation for Sustainable Mobility (DiNaMo)-active is a prospective, observational trial to characterise commuting habits among employees and students at four higher educational institutions in Hannover (Germany) and estimate their short and long-term impact on health-related and economic issues. We will use wearable activity trackers and questionnaires to examine the long-term influences of active (by foot or by bicycle) or passive (eg, private cars, motorbikes, scooters or public transportation) commuting on physical and mental outcomes among students and university employees. We will also apply more in-depth physiological measures like continuous glucose monitoring, ambulatory blood pressure recordings and particulate matter concentrations to compare the short-term effects of active versus passive commuting on physiological regulations during commuting, working and time after work.Facilitating physically active and sustainable transportation could contribute to a healthier lifestyle and reduce road traffic and greenhouse gas emissions. The way to work as a potential resource for a physically active and sustainable form of commuting is rarely studied, and our results might provide relevant information for policymakers and occupational health experts.This observational trial is prospectively registered (DiNaMo-active NCT06493006).Protocol version 1.0 (15 April 2025).